2022
DOI: 10.3390/ijms23073794
|View full text |Cite
|
Sign up to set email alerts
|

Rare Subtype of Endometrial Cancer: Undifferentiated/Dedifferentiated Endometrial Carcinoma, from Genetic Aspects to Clinical Practice

Abstract: Endometrial cancer (EC) is one of the most common gynecologic cancers worldwide. There were 417,367 newly diagnosed cases and 97,370 deaths due to this disease worldwide in 2020. The incidence rates have increased over time, especially in countries with rapid socioeconomic transitions, and EC has been the most prevalent gynecologic malignancy in Taiwan since 2012. The new EC molecular classifications of The Cancer Genome Atlas (TCGA) Research Network include clear-cell carcinoma, serous carcinoma, and carcinos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 70 publications
(123 reference statements)
0
6
0
Order By: Relevance
“…Therefore, clinicians need to place adequate emphasis on the diagnosis of the disease, which requires appropriate sampling of endometrial tissue, supported by IHC staining if necessary; otherwise, the condition can be missed or misdiagnosed as G3 EC, UESS, UNEC, or UCS. 2,19 Ganju et al 20 reported 24 cases of UEC, 10 (42%) of which were advanced at diagnosis. And 2 of them spread to uterine serosa or adnexa, 4 showed pelvic lymph node involvement, and 4 had distant metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, clinicians need to place adequate emphasis on the diagnosis of the disease, which requires appropriate sampling of endometrial tissue, supported by IHC staining if necessary; otherwise, the condition can be missed or misdiagnosed as G3 EC, UESS, UNEC, or UCS. 2,19 Ganju et al 20 reported 24 cases of UEC, 10 (42%) of which were advanced at diagnosis. And 2 of them spread to uterine serosa or adnexa, 4 showed pelvic lymph node involvement, and 4 had distant metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent gynecologic cancer is endometrial cancer [1][2][3]. In 2018, there were 121,600 new cases of this cancer diagnosed in Europe, roughly 6.6% of all malignancies found in women.…”
Section: Introductionmentioning
confidence: 99%
“…Endometrial carcinoma is also described on the basis of histology, with the most common type being endometrioid, followed by the more uncommon clear cell and serous cell (both non-endometrioid) [ 11 ]. Even more rare is the recently recognized dedifferentiated endometrial carcinoma, which tends to be more aggressive, diagnosed at a later stage, and noted to be resistant to conventional chemotherapies [ 12 ].…”
Section: Introductionmentioning
confidence: 99%